Microstructural evolution and mechanical properties in Zr–Cu–Al–Nb bulk metallic glass composites prepared by laser metal deposition. (January 2022) - Luo, Ning; Galgon, Florian; Krauß, Sebastian; Morales, Luis A.; Merle, Benoit; Zenk, Christopher H.; Körner, Carolin
Abstract: In this work, laser metal deposition (LMD), a direct energy deposition (DED) additive manufacturing technology, is used to prepare Zr59.3 Cu28.8 Al10.4 Nb1.5 bulk metallic glass composites (BMGCs). Phase constitutions and thermal behavior of LMD-processed Zr–Cu–Al–Nb samples are examined using X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The microstructure evolution parallel to the build direction is characterized in detail utilizing scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), electron probe microscopy analysis (EPMA) and electron backscatter diffraction (EBSD). Young's modulus and hardness in typical microstructures are evaluated employing nanoindentation. Within each deposited layer, a periodic microstructure, exhibiting crystalline features of three distinctly different morphologies, is observed, depending on the location within that layer. Along the build direction, the dominating microstructure of the melt pool evolves from a nearly featureless amorphous state over fine nanocrystals to coarse nanocrystals while the morphology of most micro-scale dendritic crystals changes from flower-shaped to columnar, simultaneously a coarse microstructure appearing in upper layers. The fine Al-rich phases gradually coarsen directionally parallel to the build direction. Furthermore, the correlation between microstructure and mechanical properties is investigated. This work enhances our knowledge about microstructural characteristics and mechanical properties of BMGCs in-situ fabricated by DED additive manufacturing. Highlights: Cooling rates during laser metal deposition (LMD) are found to be sufficient to obtain amorphous regions in the processed Zr–Cu–Al–Nb alloys. Heat accumulation and thermal cycling during the deposition of subsequent tracks/layers cause localized crystallization. It is concluded that LMD exhibits great potential for the production of partially amorphous bulk metallic glass composites with promising properties.